Need for redefining needs - Asadi-Lari, M.; Packham, C.; Gray, D. (2003)
Defining needs is difficult due to the inherent complexity of the concept of 'need', so it is not surprising that numerous definitions have been proposed. 'Health' consists of a wide range of characteristics so 'health needs' ought to include personal and social care, health care, accommodation, finance, education, employment and leisure, transport and access.Target-driven standards in areas of health care with a high political profile appear to be replacing the concept of universal provision and clinical need; this major change in clinical care warrants a re-evaluation of health care outcomes. Identifying who might benefit from this new approach to health care is equally important if scarce resources are to be fully and appropriately utilised. If the goal of care is 'optimal health', the key marker of success ought to be to ascertain individual patients' health care needs (HCN) and tailor services accordingly. Wide variation in the description of 'needs' directly affects policies and services intended to meet a population's health care needs. Consequently, the definition of 'needs' has important implications for healthcare provision- the more constrained the definition, the less healthcare will be made available and vice versa. This paper describes some common definitions of needs and discusses their respective benefits and disadvantages in terms of health care provision and their potential impact on health policy